PENGARUH ONLINE CUSTOMER REVIEW, BRAND IMAGE DAN KEPERCAYAAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN DEODORANT JENNSKIN DI MARKETPLACE SHOPEE - JESICA JESICA; Suhardi Suhardi (SCIENTIA JOURNAL, 2026)
This study aims to analyze the influence of online customer reviews, brand image, and consumer trust on the purchasing decisions of Jennskin deodorant products in the Shopee marketplace. The background of this research is based on the phenomenon of numerous negative customer reviews, intense brand competition, and consumer trust issues regarding product authenticity on the e-commerce platform. This study employs a quantitative causal approach. Data were collected through questionnaires distributed to 119 respondents who have purchased Jennskin deodorant on Shopee. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 25, as well as hypothesis testing through t-tests and coefficient of determination. The hypotheses in this study include the suspected influence of online customer reviews on purchasing decisions, the influence of brand image on purchasing decisions, the influence of consumer trust on purchasing decisions, and the simultaneous influence of online customer reviews, brand image, and consumer trust on purchasing decisions. Keywords: Online Customer Review, Brand Image, Consumer Trust, Purchasing Decision, Jennskin Deodorant.